KH. MUSTOFA BISRI’S HUMANISTIC HERMENEUTICS OF HADITH AS A RESPONSE TO NEO-REVIVALIST ISLAM - Muluk, Muchamad Saiful; Nikmah, Shofiatun (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
The neo-revivalist Islamic group had a rigid religious attitude, takfiri and a truth claim attitude. This attitude was born because it started from reading the hadith which was ahistorical and partial. Thus, it produced an understanding that causes more harm to humanity than its mashlahah. Oftentimes, the purpose of law was lost and the meaning was distorted. This study focused on the hadith reading method used by KH. Mustofa Bisri especially in responding to the neo-revivalist Islamic way of religion. This research focuses on the method of reading hadith in the book of Arbain al-Nawawi used by KH. Mustofa Bisri, especially in responding to the neo-revivalist way of Islam. The results showed that 1) KH Mustofa Bisri used the figure of the Prophet’s humanism as a paradigm for reading the hadith, where Gus Mus saw the prophet’s personal portrait as a whole human being who was the most humane, and respected fellow human beings; 2) KH Mustofa Bisri applies Schleiermacher’s hermeneutics in positioning the text as well as Gadamer’s hermeneutics in obtaining meanings that prioritize mashlahah values.[Kelompok islam neo-revivalis memiliki sikap keberagamaan yang kaku, rigid, takfiri dan sikap truth claim. Sikap itu lahir karena bermula dari pembacaan hadis yang ahistoris dan parsial. Sehingga menghasilkan pemhaman yang menimbulkan banyak madharat bagi kemanusiaan dibanding mashlahat-nya. Seringkali tujuan hukum menjadi hilang dan makna pun terdistorsi. Penelitian ini berfokus pada metode pembacaan hadis dalam kitab Arbain al-Nawawi yang digunakan oleh KH. Mustofa Bisri, khususnya dalam merespon cara beragama kelompok Islam neorevovalis. Hasil penelitian menunjukkan bahwa 1) KH. Mustofa Bisri menggunakan sosok humanisme Nabi sebagai paradigma pembacaannya terhadap hadis, dimana Gus Mus melihat potret pribadi nabi sebagai manusia secara utuh yang paling manusiawi, dan menghormati sesama manusia; 2) KH. Mustofa Bisri mengaplikasikan hermeneutika Schleiermacher dalam memposisikan teks sekaligus hermeneutika Gadamer dalam mendapatkan makna yang mengedepankan nilai-nilai maslahah.]